SUSCEPTIBILIDADE ANTIMICROBIANA DE AMOSTRAS DE ESCHERICHIA COLI ISOLADAS DE FRANGO INDUSTRIAL (GALLUS GALLUS DOMESTICUS - LINNAEUS, 1758) COM COLIBACILOSE - Marietto Gonçalves, G.a. [UNESP]; Andreatti, R.l. [UNESP] (Instituto Biológico, 2021)
The present study evaluated the susceptibility of Escherichia coli samples isolated from poultry with colisepticemia in midwestern São Paulo State at the Ornitopathology Laboratory of FMVZ-UNESP/Botucatu, SP. A large number of samples were found that were multi-resistant to the antibiotics tested, the less effective drugs being sulfonamide and tetracycline. All samples were susceptible to norfloxacin and gentamicin.

O presente estudo avaliou a susceptibilidade de amostras de Escherichia coli isoladas de quadros de colissepticemia aviária da região centro-oeste paulista pelo Laboratório de Ornitopatologia da FMVZ-UNESP/Botucatu, SP. Constatou-se um grande número de amostras multirresistentes aos antibióticos testados, onde as drogas menos efetivas foram sulfonamida e tetraciclina. Todas as amostras mostraram-se sensíveis a norfloxacina e gentamicina.
ANTIMICROBIAL SUSCEPTIBILITY OF SAMPLES OF ESCHERICHIA COLI ISOLATED FROM INDUSTRIAL CHICKENS (GALLUS GALLUS DOMESTICUS LINNAEUS, 1758) WITH COLIBACILLOSIS
Keywords: Escherichia coli; antibiogram; avian pathology; animal health; Escherichia coli; antibiograma; ornitopatologia; saúde animal